Ownership or Performance: What Determines Board of Directors' Turnover in Italy? - Giorgio Brunello; Clara Graziano; Bruno Parigi (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper analyses the turnover of board of directors members on a sample of companies listed on the Milan Stock Exchange in the period 1988-1996. Our aim is to investigate if board members change more frequently when company performance is poor, as the literature suggests, if this relationship is similar for C.E.O.s and other board members, and if and how the ownership structure of Italian companies affects these relationships. We use three different measures of board of directors turnovers: turnover A is the turnover of all board members; turnover B is the turnover of the President, Vice-President, C.E.O. and General Manager; finally turnover C is the turnover of C.E.O.s only. We find that changes in ownership affect turnover and that the relationship between turnover and performance is stronger in companies that have experienced a change in the controlling shareholder.
Keywords: G34; J63; 330; Board of Directors; Corporate governance; Financial agency; Arbeitsmobilität; Vorstand; Eigentümerstruktur; Corporate Governance; Unternehmenserfolg; Italien